Basal Cell Adenoma in the Parotid Gland: CT and MR Findings - Jang, Mijung (AJNR Am J Neuroradiol, 2004)
Summary: Basal cell adenoma is a rare benign salivary gland epithelial tumor, usually involving the parotid gland. We report CT and MR findings of three cases with basal cell adenoma occurring in the parotid gland. The three cases presented here demonstrate a well-circumscribed tumor, which showed a cystic and solid, or the pure solid mass. They were well enhanced after contrast matter injection. The solid portion of the mass was isoattenuated at CT, with intermediate signal intensity on T1- and T2-weighted MR images. Its cystic portion was hyperintense on both T1- and T2-weighted MR images. It had a hypointense rim on T2-weighted image.